Student attitudes to plagiarism and collusion within computer science - Dennis, Louise Abigail (Northumbria University Press, 2005)
There is a widespread perception among staff in Computer Science that plagiarism is a major problem particularly in the form of collusion in programming exercises. While departments often make use of electronic detection measures, the time consumed prosecuting plagiarism offences remains a problem. As a result departments continue to seek ways to reduce the amount of plagiarism and collusion that occurs.